Electronic structure of main-group-element-centered octahedral gold clusters - Görling, Andreas; Rösch, Notker; Ellis, D.E.; Schmidbaur, Hubert (Inorganic Chemistry, 1991)
Molecular orbital calculations have been performed for the octahedral cluster ions [(HP)Au]X (X = B, X = C, X = N) by using the first-principles self-consistent discrete-variational Xα method. The fragments Au and [(HP)Au] have also been investigated, and the interpretation of their electronic structure forms the basis for an understanding of the main-group-element-centered clusters. Furthermore, a nearest-neighbor extended Hückel model is used to aid in elucidating the electronic structure of Au. A major result, at variance with previous models for bonding in gold cluster compounds, is the prominent contribution of Au 5d orbitals, which is found to be as important as that of Au 6s orbitals. Their interplay, s-d hybridization, is symmetry-dependent and synergistic with both radial Au-ligand σ bonding and tangential Au-Au bonding. Relativistic effects strongly enhance this interaction mechanism and therefore are significant for the overall stability of the clusters. The central atom formally takes up four electrons that would otherwise reside in energetically unfavorable molecular orbitals, and it contributes to the stability of the cluster by forming radial bonds. Orbital and favorable electrostatic interactions decrease along the series X = B, C, N. However, for the boron-centered compound, repulsion between radially nonbonding Au d electron density and B 2p-derived density strongly reduces (or outweighs) the favorable interactions. The bonding interactions in the yet unsynthesized boron-centered cluster may be increased by employing more electronegative functional groups on the phosphine ligands although possibly at the expense of solvation and crystal packing problems. The flavor of the molecular orbital analysis, given here for octahedral gold clusters, notably the important role of Au 5d-6s hybridization, may be transferred to other gold cluster compounds, especially the closely related five-coordinated systems [(RP)Au]Y (Y = C, Y = N). © 1991 American Chemical Society.